Advertising and the Transformation of Screen Cultures - Florin, Bo (Film Culture in Transition, 2021)
Advertising has played a central role in shaping the history of modern media. While often identified with American consumerism and the rise of the 'Information Society', motion picture advertising has been part of European visual culture since the late nineteenth century. With the global spread of ad agencies, moving image advertisements became a privileged cultural form to make people experience the qualities and uses of branded commodities, to articulate visions of a 'good life', and to incite social relationships. Abandoning a conventional delineation of fields by medium, country, or period, this book suggests a lateral view. It charts the audiovisual history of advertising by focussing on objects (products and services), screens (exhibition, programming, physical media), practices (production, marketing), and intermediaries (ad agencies). In this way, the book develops new historical, methodological, and theoretical perspectives.